Glosa do wyroku Sądu Najwyższego z 27 lutego 2025 r., sygn. akt I USKP 97/24 (glosa częściowo krytyczna) - Urban, Agnieszka; Zalewska, Marta (Studia Prawa Publicznego, 2026)
This gloss examines the Supreme Court judgment of 27 February 2025 (case no. I USKP 97/24), which addresses the issue of verifying the declared basis for assessing social insurance contributions when business activity is commenced in atypical circumstances. The Supreme Court held that while conducting business activity constitutes a valid title for social insurance coverage, the pension authority may assess whether the declared contribution base corresponds to the entrepreneur’s actual income. The case arose from a situation in which business activity was performed for a former employer. Unlike the lower court, however, the Supreme Court did not challenge the insurance title itself. The analysis focuses on the scope and legal basis for the Social Insurance Institution’s (ZUS) interference with the declared contribution base when the fact of conducting business activity is undisputed. The authors also consider whether, and to what extent, this judgment may affect the practice of pension authorities, which often deny benefits to pregnant women who establish a business, citing alleged abuses. Finally, the gloss identifies criteria that should guide inspections of entrepreneurs to strike a balance between preventing abuse of the social security system and protecting the rights of insured persons.